Meta-analysis of the efficacy of best possible self : a positive psychology intervention - Fong, Kuan Wei (Nanyang Technological University, 2020)
Positive psychology interventions have shown promise in recent years in improving well-being. A commonly used intervention is the Best Possible Self (BPS) intervention. Does the intervention improve positive affect and reduce negative affect? The aim of this thesis and meta-analysis is to consolidate effect sizes found in randomized experimental studies of the BPS intervention and to identify moderator variables that influence the effect of the intervention. Twenty-two studies, with a total of 1719 participants, met criteria for inclusion in the analysis. Results show that the BPS intervention significantly improve positive affect and reduce negative affect. In addition, several factors moderated the effectiveness, including the specificity of the instructions, time instructions given to participants, whether the studies were administered in-person or online, and the type of control group compared to. The findings in this meta-analysis indicated that the BPS intervention is an effective intervention which can be used to improve affect.